Identification of the alcohol abuse in bankers - Rodrigues, Anália Ferraz; Quilião, Paula Lamb; Pinheiro, Lyz Soltau Missio; Carneiro, Clímaco Mallmann Gomes; Carneiro, Cláudia Fleck Gomes; Péres, Décio Passos Sampaio (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2016)
This study aimed to observe aspects related to the consumption of alcohol as a risk factor for occupational illness in workers at bank branches in the city of Alegrete - RS. In the period from May to August 2013 they were applied questionnaires in 94 bank workers who agreed to participate, of whom 58.5% were male and 41.5% female, with an average age of 41.54 years. Among the participants, 14.9% had risk consumption of alcohol, whereas 1% is considered high risk, and 1% had probable dependence. The results indicate considerable prevalence of hazardous alcohol consumption among workers of fi nancial institutions in Alegrete and highlight the need for health promotion actions of these workers.